What Neo-FPI offers toward the Muslim Community: Exploring a New Face of Islamic Activism and Populism in Indonesia - Ahalla Tsauro; Firmanda Taufiq (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2023)
Despite the image of traditional-moderate Islam in Indonesia, a religious-conservatism group such as Islamic Defenders Front (Front Pembela Islam or FPI) had colored Islamic activism and populism in Indonesia in the last two decades. This group is indeed notoriously full of controversy because of harsh approaches and having a political mission, notably during the 2017 Jakarta gubernatorial election. The series of violent approaches and opposing Pancasila ideology then lead to the disbandment of FPI at the end of 2020 through a joint ministerial decision that brought several consequences, particularly in public perception. On the one hand, some might assume that public security, peace, and tranquillity have been achieved by violence-based group, but on the other hand, some might argue that this dissolution has received public sympathy as the government seems to be more authoritative and FPI bravely keep opposing and channeling public disappointment. Afterward, in early January 2021 with a new name, Islamic Brotherhood Front (Front Persaudaraan Islam or Neo-FPI) was reborn. This study aimed at exploring how Neo-FPI responds and transforms after being dissolved constitutionally by the government and to what extent this rebirth is accepted by the Muslim community. Through Sidney Tarrow’s social movement theory, this research will assess Neo-FPI as a discourse of Islamic activism and populism through library research and will interview the group’s members. The result of the study shows that the Neo-FPI might try to attempt on humanistic approach and moderation within the religious movement. However, substantially this group will not be different from the old version like an apple that falls not far from the tree. In addition, it is interesting to see how this group coup with the pandemic situation as the group’s leader has been sentenced to jail due to legal issues.